2018
DOI: 10.21037/jtd.2018.01.32
|View full text |Cite
|
Sign up to set email alerts
|

Development of a precision multimodal surgical navigation system for lung robotic segmentectomy

Abstract: Minimally invasive sublobar anatomical resection is becoming more and more popular to manage early lung lesions. Robotic-assisted thoracic surgery (RATS) is unique in comparison with other minimally invasive techniques. Indeed, RATS is able to better integrate multiple streams of information including advanced imaging techniques, in an immersive experience at the level of the robotic console. Our aim was to describe three-dimensional (3D) imaging throughout the surgical procedure from preoperative planning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The technical challenge of segmentectomy is to perform a true anatomical and oncologic resection with safe margins. A multimodality imaging approach [89,90] to segmentectomy, using a combination of colored or fluoroscopic endoscopic [91][92][93] or physical X-ray [94,95] markings and 3D reconstructions of segmental vessels and bronchus, segments and tumor [89,96,97], helps surgeons to identify small, non-visible, and non-palpable tumors, and to anticipate individual anatomy in the surgical space and expected oncologic margins to perform oncologically effective and safe personalized tailored segmentectomy (Figure 4). These imaging tools are helpful for open segmentectomy, and even more for minimally invasive approaches, using indocyanine green and near-infrared angiography [98][99][100] to identify the intersegment plan.…”
Section: "Resecting Less" Segmentectomy For Early-stage Nsclc From Present To Futurementioning
confidence: 99%
“…The technical challenge of segmentectomy is to perform a true anatomical and oncologic resection with safe margins. A multimodality imaging approach [89,90] to segmentectomy, using a combination of colored or fluoroscopic endoscopic [91][92][93] or physical X-ray [94,95] markings and 3D reconstructions of segmental vessels and bronchus, segments and tumor [89,96,97], helps surgeons to identify small, non-visible, and non-palpable tumors, and to anticipate individual anatomy in the surgical space and expected oncologic margins to perform oncologically effective and safe personalized tailored segmentectomy (Figure 4). These imaging tools are helpful for open segmentectomy, and even more for minimally invasive approaches, using indocyanine green and near-infrared angiography [98][99][100] to identify the intersegment plan.…”
Section: "Resecting Less" Segmentectomy For Early-stage Nsclc From Present To Futurementioning
confidence: 99%
“…The use of infra-red light with green ICG [ 19 ] orients surgeons towards the inter-segmental plane with excellent precision in order to preserve healthy lung parenchyma. It has been demonstrated that a multimodal system including 3D imaging has good operative anatomical accuracy and provides more comfort, helping surgeons to make decisions when they encounter complex situations [ 27 ]. Moreover, this technique helped us to perform a picking lymphadenectomy for indolent lesions (ground-glass nodules, lesions smaller than 2 cm, slowly evolving, with low metabolic activity on a positron emission tomography scan) with good results and few long-term recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the practice of segmentectomy has expanded. Several reasons could explain this trend: firstly, the increased incidence of early stage LC managed by surgery, secondly, the ageing of patients with localized LC, and, thirdly, the development of multimodal surgical navigation systems and minimally invasive surgery (4)(5)(6)(7)(8)(9).…”
Section: Original Articlementioning
confidence: 99%